2018
DOI: 10.3138/ptc.2016-58
|View full text |Cite
|
Sign up to set email alerts
|

What Do Patients with Chronic Spinal Pain Expect from Their Physiotherapist?

Abstract: Evidence has suggested that patients' expectations influence the clinical course when they present with low back pain (LBP). However, little empirical evidence has outlined the nature of these expectations. The aim of this study was to describe LBP patients' expectations of physiotherapy. Seventy-nine adult patients who had LBP for more than 16 weeks and were referred for physiotherapy at two hospital physiotherapy departments in St. John's, Newfoundland and Labrador, were included. They filled out a questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 22 publications
2
16
0
1
Order By: Relevance
“…The PACT treatment approach can address physical therapists' barriers to using psychological techniques, 25 as well as patients' concerns about finding a credible treatment offering aspects of care they value. 17 As physical therapy is a common treatment for CLBP and millions of patients are referred to physical therapists every year, even small additional benefits could have a considerable impact for patients, healthcare providers, and society. Next steps might include refining the training and support for physical therapists, as well as investigating whether to select patients and/ or provide additional treatment sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PACT treatment approach can address physical therapists' barriers to using psychological techniques, 25 as well as patients' concerns about finding a credible treatment offering aspects of care they value. 17 As physical therapy is a common treatment for CLBP and millions of patients are referred to physical therapists every year, even small additional benefits could have a considerable impact for patients, healthcare providers, and society. Next steps might include refining the training and support for physical therapists, as well as investigating whether to select patients and/ or provide additional treatment sessions.…”
Section: Discussionmentioning
confidence: 99%
“…15 Recent reviews have concluded that this could be rectified with additional training and support. 16 Other findings have suggested patients with CLBP want to discuss personal issues with their physical therapist, 17 although many physical therapists perceive they lack the skills or confidence to address these concerns. 14 This highlights the need to develop psychologically informed interventions that are suitable for physical therapists and the training to help them provide it.…”
mentioning
confidence: 99%
“…The ndings of this survey point to challenges for clinicians in the management of their patients with back pain, and align with ndings from a clinical sample in the same jurisdiction. [21] These challenges lie with commonly held beliefs that run contrary to evidence-based management of LBP. Most notably, substantial proportions of people believe that they should stop working and rest, that their backs will forever be weak, that there is no real treatment and that imaging is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Physical assessment, education and advice are built on guideline recommendations and in line with expectations from physiotherapists of patients with back pain 23–25 35–37. Education and advice are designed to improve participants’ understanding of the biopsychosocial nature of low back pain by presenting information on the nature of pain biology,38 address erroneous beliefs about back pain (eg, that low back pain is always associated with pathology) and outline links between low back pain and health behaviour risks (weight, smoking, and so on).…”
Section: Methods and Analysismentioning
confidence: 99%